Herding behavior in the indonesia stock exchange around the covid-19 pandemic - Warganegara, Siti Fareta Anggia; Warganegara, Dezie Leonarda (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study investigates the occurrence of herding behaviour on the Indonesian Stock Exchange during the COVID-19 pandemic. This study finds that herding action happened exclusively in the Indonesian stock market before the COVID-19 pandemic. In contrast, the herding behaviour in the Indonesian stock market decreased during COVID-19 pandemic. Further tests reveal that the decrease of herding behaviour was even higher when the market experienced extreme market return movements in both directions. All the findings stand when using an alternative proxy for the dependent variable in the robustness tests of this study. The results imply that Indonesian investors are more cautious and logical in their investment decision-making during the COVID-19 pandemic, owing to the certainty of the pandemic's detrimental impacts on the economy and, thus, stock prices.